Qualitative Evaluation of the Project P.A.T.H.S.: Findings Based on Focus Groups with Student Participants - Daniel T. L. Shek; Catalina S. M. Ng (The Scientific World Journal)
This paper reports a qualitative evaluation study conducted to explore the perceptions of students who joined the Tier 1 Program of the Project P.A.T.H.S. A total of 92 students were randomly selected to participate in 10 focus groups, which provided qualitative data for the study. With specific focus on how the informants described the program, the descriptors used were primarily positive; the metaphors named by the informants that could stand for the program were basically positive. Program participants also perceived the program to be beneficial in different psychosocial domains. The present study lends further support to the effectiveness of the Tier 1 Program of the Project P.A.T.H.S. in promoting holistic development in Chinese adolescents.